Mental Health Level among Children with Hearing Disability: A comparative field study between school merged children and non- merged in Ain Temouchent, Algeria - Kerroum, Mouffok; Megdad, Amira (Journal of Educational and Psychological Sciences, 2020)
The current research aims to reveal the level of mental health of the hearing impaired, and then compare the health levels of the two groups of hearing impaired (hearing impaired school-integrated and the hearing impaired not school-integrated). The research was based on the SCL-90-R (Symptoms Check List) by applying it to a sample of hearing-impaired children who were deliberately selected, as it consisted of 40 students from the deaf and dumb center in Ain Temouchent. They are divided into two groups (23 students who are included in ordinary schools) and (23 students who are not included). the results showed that there are differences in the level of mental health between the two groups of hearing impaired, which means that the group of hearing impaired people who are not included is characterized by a high level of mental health problems. Based on these results, a set of recommendations and suggestions were reached, such as the necessity of paying attention to the process of school integration through creating the school environment and proposing comprehensive survey studies on this category in society in general and the school in particular, as well as proposing treatment and other indicative programs to facilitate the school integration process.